Imaging features and clinic value of mri and ct in diagnosis of clear cell renal cell carcinoma - YANG,Zhongjie (2022)
Abstract To investigate the imaging features and clinic value of magnetic resonance imaging (MRI) and computed tomography (CT) in the diagnosis of clear cell renal cell carcinoma (ccRCC). 139 RCC patients underwent MRI and CT examination before surgery, and the sensitivity, specificity, accuracy, positive and negative predictive values of MRI and CT in diagnosing ccRCC were analyzed and compared. There were 93 true-positive, 11 false-positive, 11 false-negative and 24 true-negative in MRI screening with sensitivity, specificity, accuracy, positive predictive value and negative predictive value of 89.42%, 68.57%, 84.17%, 89.42% and 68.57% respectively. Whereas there were 72 true-positive, 4 false-positive, 32 false-negative and 31 true-negative in CT screening with the sensitivity, specificity, accuracy, positive predictive value and negative predictive value of 69.23%, 88.57%, 74.10%, 94.74% and 49.21% respectively. The sensitivity and negative predictive value of MRI were better than those of CT, while the specificity of CT was better than that of MRI. MRI and CT have respective advantages in the diagnosis of ccRCC. The sensitivity and negative predictive value of MRI are superior to those of CT, while the specificity of CT is superior to that of MRI. Clinically, different examinations are selected according to different situations.